The outpatient treatment of eating disorders : a guide for therapists, dietitians, and physicians - Mitchell, James E. (James Edward), 1947- (University of Minnesota Press, 2001)
This volume balances general and pathology-specific research to emphasize outpatient treatment. The contributors provide an overview of the full range of eating disorders and offer clinical recommendations for a comprehensive treatment plan for patients with these disorders.